2001
DOI: 10.1163/156856201753252525
|View full text |Cite
|
Sign up to set email alerts
|

Protein adsorption on preadsorbed polyampholytic monolayers

Abstract: The adsorption behaviour of five different globular proteins on pure silicon substrates and on preadsorbed polyampholytic monolayers has been investigated as a function of protein concentration.. The prelayers were prepared by adsorption of the ampholytic diblock copolymer poly(methacrylic acid)-block-poly((dimethylamino)ethyl methactylate) (PMAA-b-PDMAEMA). This polyampholyte adsorbs in densely packed micelles directly from aqueous solution. Ellipsome-try was used to determine the amount of adsorbed polyampho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Our previous biosensor work has shown that these materials have excellent nonfouling characteristics only when the oppositely charged monomer subunits are present as a statistical copolymer mixture at the molecular level . Others have also completed surface-based investigations, confirming that polyampholyte polymer systems have nonfouling properties. …”
Section: Introductionmentioning
confidence: 97%
“…Our previous biosensor work has shown that these materials have excellent nonfouling characteristics only when the oppositely charged monomer subunits are present as a statistical copolymer mixture at the molecular level . Others have also completed surface-based investigations, confirming that polyampholyte polymer systems have nonfouling properties. …”
Section: Introductionmentioning
confidence: 97%
“…Our previous work demonstrated that this concept could be applied to polyampholyte statistical copolymer brushes. These polymer brush coatings have been demonstrated to be nonfouling, as long as the individual charged units were homogeneously mixed at the molecular level. This approach has since been adapted by others in additional polymer brush systems. Similarly, investigators have examined polyampholyte polymer coatings that are adsorbed to surfaces rather than being grafted from the surface as an alternative mechanism for creating nonfouling surface coatings. , …”
Section: Introductionmentioning
confidence: 99%
“…28−30 Similarly, investigators have examined polyampholyte polymer coatings that are adsorbed to surfaces rather than being grafted from the surface as an alternative mechanism for creating nonfouling surface coatings. 31,32 Polyampholyte hydrogels and microgels have also been widely investigated as temperature and/or pH responsive systems useful for carrying and delivering drugs and proteins. 33−36 Given this application, it is often desirable for the hydrogel system to have protein adsorption capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…This article will report the desorption behaviour of a diblock polyampholyte PMAA-b-PDMAEMA, poly(metha-crylic acid)-block-poly((dimethylamino)ethyl methacrylate), The used diblock system with a molecular weight of 15000 g/mol and a block ratio of PMAA: PDMAEMA 33 :67 is well characterized and known to adsorb in highly regular adsorbed structures [32]. Previous studies report also on the high stability of these polyampholyte layers under treatment with phosphate buffered protein solutions [33]. High adsorbed amounts of around 16 mg/m 2 on silicon substrates and regular adsorbed structures facilitate investigations on the desorption by ellipsometry and atomic force microscopy (AFM).…”
Section: Introductionmentioning
confidence: 99%